Effect of Wear-Resistant Tape Layers on Torsional Characteristics of Unbonded Flexible Pipes Under Internal Pressure - LUO Chunmiao, FU Shixiao, ZHANG Mengmeng, CHEN Kunpeng, CUI Xiaoxuan (Shanghai Jiaotong Daxue xuebao)
Unbonded flexible pipe has been widely used in the offshore oil and gas industry and its torsional balance plays an important role in safety insurance during the whole service life. However, there are still torsional imbalances due to simplifying assumptions in the current analytical theory. To improve the accuracy of torsion simulation and reduce the impacts on the practical applications of the pipelines, this paper focuses on the wear-resistant layer neglected in previous studies. Based on theoretical derivation, in combination with the finite element method, a correction algorithm for the torsional stiffness and elastic modulus of the tape layer is developed to investigate the effect of tape layer stacking on the overall torsion of the unbonded flexible pipe. The results show that overall torsion results obtained by using the corrected elastic modulus of the tape layer are closer to the test results, which have guiding significance for practical applications. Further sensitivity research shows that the width of the tape layer is positively correlated with the flexible pipe torsion angle, while the tape laying angle is negatively correlated with the overall torsion angle. With an increase in the stacking ratio of the tape, the pipeline torsion angle decreases.